Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Mono- and sesquiterpenoid fingerprinting: A powerful and streamlined solution for pine nut authentication - B. Torres-Cobos; S. Nicotra; C. Asensio-Manzano; N. Aletà; A. Teixidó; M. Rovira; A. Romero; F. Guardiola; S. Vichi; A. Tres (Food Chemistry, 2025)

Meeting the challenge of varietal and geographical authentication of hazelnuts through lipid metabolite fingerprinting - B. Torres-Cobos; S.B. Nicotra; M. Rovira; A. Romero; F. Guardiola; A. Tres; S. Vichi (Food Chemistry, 2025)

Deceleration captured by InSAR after local stabilization works in a slow-moving landslide: the case of Arcos de la Frontera (SW Spain) - Guadalupe Bru; Pablo Ezquerro; Jose M. Azañón; Rosa M. Mateos; Meaza Tsige; Marta Béjar-Pizarro; Carolina Guardiola-Albert (Landslides, 2024)
Interferometric synthetic aperture radar (InSAR) is a remote sensing tool used for monitoring urban areas affected by geological hazards. Here we analysed the effectiveness of stabilization works on a slow-moving landslide in Arcos de La Frontera (Cádiz, Spain) using a persistent scatterer interferometric approach. The works consisted on jet grouting of cement-based injections and were applied locally to stabilize the most damaged neighbourhood. We processed a large stack of Sentinel-1 SAR satellite acquisitions covering the period January, 2016, to March, 2023, and obtained surface velocity and displacement trends measured along the line of sight (LOS) of the satellite on both ascending and descending orbits. The results show a clear deceleration of the landslide head after mid-2018, suggesting the local stabilization works were effective after that time. Prior to mid-2018, the maximum LOS velocity of the landslide head was 2.2 cm/year in ascending orbit and 1.3 cm/year in the descending orbit, decreasing to 0.43 cm/year and 0.23 cm/year, respectively. The InSAR results were compared to in-situ monitoring data and revealed that the extent of the stabilization has influenced a much larger area beyond the zone of the local interventions. Overall, InSAR has proved a powerful and versatile tool to be implemented in operational geotechnical monitoring.

Enhancing groundwater management with GRACE-based groundwater estimates from GLDAS-2.2: a case study of the Almonte-Marismas aquifer, Spain - C. Guardiola-Albert; N. Naranjo-Fernández; J. S. Rivera-Rivera; J. M. Gómez Fontalva; H. Aguilera; F. Ruiz-Bermudo; M. Rodríguez-Rodríguez (Hydrogeology Journal, 2024)
The Almonte-Marismas aquifer, southwestern Spain, is a critical ecohydrogeological system that features extensive groundwater monitoring. This study investigates the utility of gravity recovery and climate experiment (GRACE) satellite data, specifically obtained from the global land data assimilation system (GLDAS) version 2.2, for assessing groundwater storage variations in the Almonte-Marismas aquifer. The presented research emphasizes the practical application of readily available GLDAS products that do not require data preprocessing. The study validates the GLDAS-2.2-based ready-to-use groundwater storage (GWS) time series by correlating it with precipitation and piezometric information, highlighting its effectiveness in medium-scale aquifers. The results reveal a strong agreement between GLDAS-2.2-derived GWS anomalies and in-situ measurements, confirming GLDAS-2.2’s potential for assessing aquifer depletion. The study discusses the consistency of seasonal variations in groundwater levels and GLDAS-2.2 data, emphasizing their close alignment with precipitation and pumping activities. Importantly, the study introduces GLDAS-2.2-derived volumetric groundwater storage (VGWS) as a valuable calibration parameter for numerical groundwater flow models, enhancing their accuracy over time. Moreover, the analysis reveals disparities in annual recharge values between GLDAS-2.2-derived data and the soil-water mass balance. These variations suggest the importance of additional inputs to precipitation, possibly related to subsurface or lateral connections. Overall, this study contributes to the ongoing discourse on the practical applications of GLDAS-2.2-derived GWS data in groundwater management, offering insights into its effectiveness in diverse hydrogeological settings, particularly in areas that lack monitoring infrastructure.

Investigating isotopic markers for hazelnut geographical authentication: Promising variables and potential applications - B. Torres-Cobos; M. Rosell; A. Soler; M. Rovira; A. Romero; F. Guardiola; S. Vichi; A. Tres (Food Chemistry, 2024)

Uncovering microplastics contamination in canned seafood - Diogo M. Silva; C. Marisa R. Almeida; Francisco A. Guardiola; Rúben Pereira; Sabrina M. Rodrigues; Sandra Ramos (Food Chemistry, 2024)

Prospective exploration of hazelnut's unsaponifiable fraction for geographical and varietal authentication: A comparative study of advanced fingerprinting and untargeted profiling techniques - B. Torres-Cobos; B. Quintanilla-Casas; M. Rovira; A. Romero; F. Guardiola; S. Vichi; A. Tres (Food Chemistry, 2024)

Groundwater Abstraction has Caused Extensive Ecological Damage to the Doñana World Heritage Site, Spain - Andy J. Green; Carolina Guardiola-Albert; Miguel Ángel Bravo-Utrera; Javier Bustamante; Antonio Camacho; Carlos Camacho; Eva Contreras-Arribas; José L. Espinar; Teresa Gil-Gil; Iván Gomez-Mestre; Javier Heredia-Díaz; Claus Kohfahl; et al. (Wetlands, 2024)
Acreman et al. (Wetlands 42:63, 2022) reviewed evidence for ecological damage to the Doñana wetlands (UNESCO World Heritage Site [WHS] and Ramsar site), Spain, associated with intensification of groundwater use, particularly for agriculture. Acreman et al. presented a multistep methodology for evidence-based risk assessment that involves identification of conservation issues, and a systematic review of scientific evidence for ecological damage and its causes. However, they involved few local scientists, used a questionable methodology in stakeholder selection and involvement, used a flawed conceptual framework, and an incomplete literature review. We propose improvements to their methodology. They overlooked or misinterpreted key evidence, and underestimated the impacts that abstraction for irrigation for red fruits (mainly strawberries), rice and other crops has had on Doñana and its biodiversity. They reported groundwater level depletion of up to 10 m in the deep aquifer, but wrongly concluded that there is no evidence for impacts on the natural marsh ecosystem, the dune ponds or the ecotone. Groundwater drawdowns are actually up to 20 m, and have inverted the formerly ascending vertical hydraulic gradient in discharge areas. Phreatic levels have been lowered from 0.5 to 2 m in some areas. Groundwater abstraction has caused multiple ecological impacts to temporary ponds and marshes in the WHS, as well as to terrestrial vegetation, and should be urgently reduced. Furthermore, Acreman et al. focused on groundwater quantity while overlooking the importance of severe impacts on quality of both surface and groundwater, intimately connected to the use of agrochemicals for irrigated crops.

Analysis of SAR-derived products to support emergency management during volcanic crisis: La Palma case study - P. Ezquerro; G. Bru; I. Galindo; O. Monserrat; J.C. García-Davalillo; N. Sánchez; I. Montoya; R. Palamà; R.M. Mateos; R. Pérez-López; E. González-Alonso; R. Grandin; et al. (Remote Sensing of Environment, 2023)

Reward and fictive prediction error signals in ventral striatum: asymmetry between factual and counterfactual processing - A. Santo-Angles; P. Fuentes-Claramonte; I. Argila-Plaza; M. Guardiola-Ripoll; C. Almodóvar-Payá; J. Munuera; P. J. McKenna; E. Pomarol-Clotet; J. Radua (Brain Structure and Function, 2021)

Relevance of spatio-temporal rainfall variability regarding groundwater management challenges under global change: case study in Doñana (SW Spain) - N. Naranjo-Fernández; C. Guardiola-Albert; H. Aguilera; C. Serrano-Hidalgo; M. Rodríguez-Rodríguez; A. Fernández-Ayuso; F. Ruiz-Bermudo; E. Montero-González (Stochastic Environmental Research and Risk Assessment, 2020)

Vitamin D3 affects innate immune status of European sea bass (Dicentrarchus labrax L.) - M. Dioguardi; F. A. Guardiola; M. Vazzana; A. Cuesta; M. A. Esteban; M. Cammarata (Fish Physiology and Biochemistry, 2017)

Mercury Accumulation, Structural Damages, and Antioxidant and Immune Status Changes in the Gilthead Seabream (Sparus aurata L.) Exposed to Methylmercury - F. A. Guardiola; E. Chaves-Pozo; C. Espinosa; D. Romero; J. Meseguer; A. Cuesta; M. A. Esteban (Archives of Environmental Contamination and Toxicology, 2016)

Molecular mechanisms by which white tea prevents oxidative stress - C. Espinosa; F. Pérez-Llamas; F. A. Guardiola; M. A. Esteban; M. B. Arnao; S. Zamora; J. A. López-Jiménez (Journal of Physiology and Biochemistry, 2014)

Enrichment of gilthead seabream (Sparus aurata L.) diet with microalgae: effects on the immune system - Rebeca Cerezuela; Francisco Antonio Guardiola; José Meseguer; M. Ángeles Esteban (Fish Physiology and Biochemistry, 2012)

Characterization of nine polymorphic microsatellite loci for the calcareous sponge Paraleucilla magna Klautau et al. 2004 introduced to the Mediterranean Sea - G. Agell; J. Frotscher; M. Guardiola; M. Pascual; M. J. Uriz (Conservation Genetics Resources, 2012)

Centaurea tripontina (Compositae), a new species from the Pre-Pyrenean mountains, Spain - J. López-Alvarado; L. Sáez; R. Filigheddu; M. Guardiola; A. Susanna (Plant Biosystems, 2012)

Habitat fragmentation causes immediate and time‐delayed biodiversity loss at different trophic levels - Jochen Krauss; Riccardo Bommarco; Moisès Guardiola; Risto K. Heikkinen; Aveliina Helm; Mikko Kuussaari; Regina Lindborg; Erik Öckinger; Meelis Pärtel; Joan Pino; Juha Pöyry; Katja M. Raatikainen; et al. (Ecology Letters, 2010)
Ecology Letters (2010) 13: 597–605 Abstract Intensification or abandonment of agricultural land use has led to a severe decline of semi‐natural habitats across Europe. This can cause immediate loss of species but also time‐delayed extinctions, known as the extinction debt. In a pan‐European study of 147 fragmented grassland remnants, we found differences in the extinction debt of species from different trophic levels. Present‐day species richness of long‐lived vascular plant specialists was better explained by past than current landscape patterns, indicating an extinction debt. In contrast, short‐lived butterfly specialists showed no evidence for an extinction debt at a time scale of c. 40 years. Our results indicate that management strategies maintaining the status quo of fragmented habitats are insufficient, as time‐delayed extinctions and associated co‐extinctions will lead to further biodiversity loss in the future.